Treatment of heavy metals containing wastewater using biodegradable adsorbents: A review of mechanism and future trends. (May 2022) - Anderson, A.; Anbarasu, A.; Pasupuleti, Raghavendra Rao; Manigandan, Sekar; Praveenkumar, T.R.; Aravind Kumar, J.
Abstract: The direct disposal of industrial effluents into the aquatic system is considered as a significant environmental hazard in many countries. Because of poisonous chemicals, substantial volumes of effluent release, as well as the lack of adequate of conventional treatment methodologies, industrial effluent treatment is extremely difficult. Numerous researchers have been interested in adsorption technology for its high efficiency of pollutant removal, low cost, and abundantly available adsorbent. Various adsorbent materials, both natural and modified form, have been widely used for the removal of toxic contaminants from industrial effluent. This paper highlights recent advancements in multiple modification types to functionalize the adsorbent material, resulting in higher adsorption capacity on various toxic pollutants. This review provides an overview of the adsorption mechanism and parameters (pH, adsorbent dosage, initial concentration, temperature and interaction time), which influencing the removal efficiency of adsorbents. Furthermore, this review compiles the desorption study to recover the adsorbent and improve the cycle's financial viability. This review provides a concise overview of the future directions and outlook in the framework of adsorbent application for industrial wastewater treatment. Graphical abstract: Image 1 Highlights: Adsorption technology has received increased attention for organic pollutants removal. Recent research progress on surface modification of adsorbent was reviewed. Mechanism and key parameters controlling the adsorption performance have been discussed. Regeneration study and outlook for future research are proposed.